A customizable UHF RFID-Reader for RFID-S Testing Applications - Hofmann, Andreas; Brenk, Daniel; Boehme, Andreas; Cilek, Fatih; Ferizi, Alban; Weigel, Robert (IEEE Topical Conference on Wireless Sensors and Sensor Networks, 2011)
This paper describes a custom-built UHF RFID-Reader-Device with functionality to send and receive EPCglobal custom commands. It can be used to access enhanced capabilities in transponders, for example readout of integrated sensors. The device was implemented using a Xilinx FPGA and is fully controllable from a PC through a customizable MATLAB-Interface. This enables a step by step test of newly developed tags. All mandatory EPCglobal commands are implemented as well as EPC custom command capability.
elib2cris::1512001600,hofmann2011
Keywords: Graphical user interfaces; Protocols; Radiation detectors; Radiofrequency identification; Software; Transceivers